Ethnopharmacological Use of Medicinal Plants for Open Wounds among the Mandar Community in Lontar Timur, Kotabaru Regency - Nabila Sativa; Muhammad Anshari; Tyas Setia Nugraha (UrbanGreen, 2026)
Traditional medicinal plant knowledge remains an important component of community health practices, including wound management. This study aimed to document ethnopharmacological knowledge among the Mandar community in Lontar Timur, Kotabaru Regency, regarding medicinal plants used for open wounds. An exploratory descriptive study with a qualitative approach was conducted through semi-structured interviews with 16 informants and one traditional healer (sandro) as a key informant. Informants were selected using purposive and snowball sampling. Data were analyzed descriptively through data reduction, data presentation, and conclusion drawing. Four medicinal plants were identified: Chromolaena odorata, Allium cepa L., Curcuma longa L., and Gynura procumbens (Lour.) Merr. C. odorata was the most frequently reported plant, mentioned by all informants, while leaves were the most commonly used plant part and most plant materials were obtained from wild plants around the community. Traditional preparation included hand-crushing, squeezing, pounding, grating, boiling, chewing, and heating. The findings indicate that wound-related plant knowledge among the Mandar community represents an integrated local health knowledge system shaped by environmental availability, empirical experience, belief, and intergenerational transmission.